2020
DOI: 10.1007/s42770-020-00254-9
|View full text |Cite
|
Sign up to set email alerts
|

β-Lapachone enhances the antifungal activity of fluconazole against a Pdr5p-mediated resistant Saccharomyces cerevisiae strain

Abstract: Objectives The aim of this study was to evaluate the ability of lapachones in disrupting the fungal multidrug resistance (MDR) phenotype, using a model of study which an azole-resistant Saccharomyces cerevisiae mutant strain that overexpresses the ATPbinding cassette (ABC) transporter Pdr5p. Methods The evaluation of the antifungal activity of lapachones and their possible synergism with fluconazole against the mutant S. cerevisiae strain was performed through broth microdilution and spot assays. Reactive oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…Pdr5 is an ABC transporter which pumps out a series of structurally unrelated compounds, including azoles and rhodamine (Prasad and Goffeau, 2012 ; Shekhar‐Guturja et al ., 2016b ; de Moraes et al ., 2020 ). Consistent with previous studies (Lamping et al ., 2007 ; Prasad and Goffeau, 2012 ), we also confirmed that fluconazole is a substrate of Pdr5.…”
Section: Resultsmentioning
confidence: 99%
“…Pdr5 is an ABC transporter which pumps out a series of structurally unrelated compounds, including azoles and rhodamine (Prasad and Goffeau, 2012 ; Shekhar‐Guturja et al ., 2016b ; de Moraes et al ., 2020 ). Consistent with previous studies (Lamping et al ., 2007 ; Prasad and Goffeau, 2012 ), we also confirmed that fluconazole is a substrate of Pdr5.…”
Section: Resultsmentioning
confidence: 99%
“…Oroidin, a sponge-derived alkaloid, inhibited R6G efflux by 60% at 200 μM [ 27 ]. Beta-lapachone, a naphthoquinone obtained from Tabebuia sp., inhibited Pdr5p activity by 79.4% at 100 μg/mL [ 28 ]. In this study, it was observed that digoxin derivatives inhibited R6G efflux by 76.65–100%.…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of the coumarins was predicted in silico using OSIRIS Property Explorer [23], which provides information regarding mutagenic, tumorigenic, irritant, and reproductive effects, and GUSAR (General Unrestricted Structure-Activity Relationships), which provides a LD 50 (lethal dose to 50% of a given population) of the substances in rats, considering four routes of administration (intraperitoneal, intravenous, oral, and subcutaneous) [24].…”
Section: In Silico Toxicity Predictionmentioning
confidence: 99%